Selected Lectures of the 19th International Workshop on Neonatology and Pediatrics; Cagliari (Italy); October 18-21, 2023 - Various Authors, — (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2023)
Selected Lectures of the 19th International Workshop on Neonatology and Pediatrics; Cagliari (Italy); October 18th-21st, 2023 FROM WOMB TO AGING, FROM MEDICAL HISTORY TO ARTIFICIAL INTELLIGENCE The Workshop has been organized with the patronage of UENPS (Union of European Neonatal and Perinatal Societies), UMEMPS (Union of Middle-Eastern and Mediterranean Pediatric Societies), SIP (Italian Society of Pediatrics), SIN (Italian Society of Neonatology), SIAIP (Italian Society of Pediatric Allergology and Immunology), SIPO (Italian Society of Hospital Pediatricians), SI-DOHaD (Italian Society of DOHaD [Developmental Origins of Health and Disease]), SIBioC (Italian Society of Clinical Biochemistry), SIPPS (Italian Society of Preventive and Social Pediatrics), S.I.P.Ped. (Italian Society of Pediatric Psychology), SIGIA (Italian Society of Gynecology of Infancy and Adolescence), CONAPP (Italian Association of Chiefs of Pediatric Divisions), SIN-INF (Italian Society of Neonatal Nursing), IAPS (Italian Arabian Society of Pediatrics), Alfred Nobel’s Study Center, GNNNP (Norman Group of Neonatal and Pediatric Nephrology), IRPS (Italian Romanian Pediatric Society), RSP (Romanian Society of Pediatrics), IPMC (International Pedia Mediterranean Conference). LECT 1. NEW PERSPECTIVES IN PERINATAL MEDICINE • G. Monni, R.M. Ibba, F. Murgia (Cagliari, Italy) LECT 2. NEONATAL RESPIRATORY CARE IN EUROPE: WHERE ARE WE NOW? • C. Moretti, C. Gizzi (Rome, Italy) LECT 3. EPIGENETICS AS A BRIDGE BETWEEN EARLY NUTRITION AND LONG-TERM HEALTH AND TARGET FOR DISEASE PREVENTION • U. Simeoni (Lausanne, Switzerland) LECT 4. THE STUDY OF THE MICROBIOME: A MULTIOMICS APPROACH • A. Fasano (Boston, MA, USA, and Salerno, Italy) LECT 5. MONOCLONAL ANTIBODIES IN RSV PREVENTION: CALENDAR OF IMMUNIZATION • M. Agosti, S. Perniciaro (Varese, Italy) LECT 6. AUXOLOGICAL EVALUATION OF TWINS: THE MAZE OF DEFINITIONS AND THE NEW INTERNATIONAL CHARTS • E. Bertino, S. Deantoni, F. Giuliani, G. Migliaretti, A. Coscia, S. Gandino, I. Stura, J. Villar (Turin, Italy, and Oxford, United Kingdom) LECT 7. VITAMIN K INSUFFICIENCY AND THE PROPHYLAXIS STRATEGY IN HEALTHY TERM INFANTS: A MULTICENTER STUDY • S. Perrone, G. De Bernardo, V. Beretta, M. Giordano, G. D’Amato, G. Buonocore (Parma, Naples, Bari and Siena, Italy) LECT 8. MILK FORMULA: CRITERIA FOR A RESPONSIBLE CHOICE • L. Maggio (Rome, Italy) LECT 9. BREAST MILK: A WORLD OF WONDER • L. Orfeo, S. Luciani, R. Arena (Rome, Italy) LECT 10. BREAST MILK, “OMICS” AND SKIN • A. Dessì, R. Pintus, A. Bosco, V. Fanos (Cagliari, Italy) LECT 11. PERINATAL BACTERIA: A WORLD TO DISCOVER EVEN IN THE MOTHER’S MILK • V. Fanos (Cagliari, Italy) LECT 12. ORGANIC MILK • S. Picone, P. Paolillo (Rome, Italy) LECT 13. NEONATAL NUTRITION AND IMMUNITY • F. Mosca, L. Giannì (Milan, Italy) LECT 14. BIOMARKERS FOR NEONATAL INFECTIONS AND SEPSIS • M. Mussap (Cagliari, Italy) LECT 15. PERINATAL INFLAMMATION • C. Loddo, R. Pintus, V. Fanos (Cagliari, Italy) LECT 16. PERINATAL AND NEONATAL ANTIBIOTICS AND MICROBIOTA • N. Laforgia, R. Panza, M.E. Baldassarre (Bari, Italy) LECT 17. PROBIOTICS IN NEONATAL INTENSIVE CARE: DREAM OR REALITY? • A. Dotta, D.U. De Rose (Rome, Italy) LECT 18. LOW-FIELD BENCHTOP NMR TO DISCOVER EARLY-ONSET SEPSIS • C. Napoli (Milan, Italy)